Continuous optical chlorophyll-a and turbidity data along RV SONNE cruise SO289 - Oelker, Julia; Achterberg, Eric Pieter; Browning, Thomas J; Liu, Haoran; Voß, Daniela; Wollschläger, Jochen; Yuan, Zhongwei (PANGAEA, 2024)
Underway optical chlorophyll-a and turbidity data were collected along the cruise track with Sea-Bird Scientific ECO FLNTU sensors installed within two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). The SMBs measure alternatingly. While one box is measuring, the other one is being cleaned. At the beginning of the transect, the boxes switched to operation every three hours, later, while the ship is transecting the Pacific Gyre, the cleaning interval was changed to only every 24 hours. The water inlet for the SMBs is at about 4 m depth. The data were quality controlled and the chlorophyll-a data were additionally calibrated using discrete water samples. In situ chlorophyll-a samples were collected by the scientific party from Niskin bottles during CTD stations and underway using a tow fish. Chlorophyll-a of these samples was determined in the lab on board using a bench top fluorometer. Details on all quality control steps, the calibration, as well as a comparison to satellite data can be found in the data processing report. The resulting data set contains the original data and corresponding quality flags and, in case of chlorophyll-a, additionally the calibrated data plus quality flag. The data source is given through the name of the active SMB. The data set contains data during transect and station. We recommend to use ship's speed to filter for only transect data.
Keywords: chlorophyll-a; DAM; Fluorescence; ICBM; turbidity; Underway Measurement